The Progressivity of Farmers’ Terms of Trade in Accelerating Fiscal Policy for Poverty Alleviation Programs in Gorontalo Province - Fitri Hadi Yulia Akib; Syarwani Canon; Mahludin H. Baruwadi; Irawati Abdul; Mohammad Zubair Hippy; Mahyudin Humalanggi; Alfred Salindeho; Siti Rahmatia Machieu (Jambura Agribusiness Journal, 2026)
Fiscal policy plays a strategic role in promoting economic stability and poverty reduction in agriculture, yet rising Farmers’ Terms of Trade do not always translate into lower farmer poverty. This study contributes by clarifying this paradox and assessing whether fiscal policy effectively improves farmers’ welfare outcomes. This study aims to examine the progressivity of NTP and to analyze the extent to which NTP mediates the impact of agricultural fiscal policy on poverty reduction, given that poverty rates are predominantly concentrated among farming communities. The data used in this research is panel data comprising six districts/cities in Gorontalo Province over a ten-year period from 2015 to 2024. The data analysis methods employed include descriptive analysis and panel data path analysis. Before conducting the path analysis, the data were transformed using natural logarithms and standardized values to ensure that the beta coefficients from the equations could be used as path coefficients. The findings reveal that: (1) The progress of NTP in Gorontalo Province tends to remain above 100%, which indicates that farmers benefit from their farming activities. However, this figure does not necessarily represent that farmers are economically prosperous, as the surplus (profit/income) between farming revenue and farming costs often remains insufficient compared to the poverty line. This results in the phenomenon of high NTP values alongside persistent and significant levels of poverty. (2) The General Allocation Fund (DAU) has a positive but insignificant effect on NTP in Gorontalo Province. The Special Allocation Fund (DAK) also has a positive but insignificant effect on NTP. Similarly, NTP has a negative but insignificant effect on poverty levels in the province. Both DAU and DAK exhibit negative but insignificant direct effects on poverty. Furthermore, the indirect effects of DAU and DAK on poverty through NTP are also negative but statistically insignificant.